COGNITIVE MODELS FOR STYLISTIC ANALYSIS - Husanova Dilshoda Abduganiyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article explores the application of cognitive stylistics in literature analysis, focusing on the utilization of cognitive models to deepen interpretation and understanding. It reviews existing literature on cognitive linguistics and its relevance to stylistic analysis, proposes a methodology for applying cognitive models, presents findings from a study employing this approach, and offers recommendations for future research and teaching practices in literature.